SMART GOVERNANCE SEBAGAI PILAR UTAMA KOTA CERDAS: ANALISIS PROGRAM CIREBON JEH (JARINGAN EDUKASI HUKUM) - Fetty Zelia Fitriani; Akhmad Khalimy; Jefik Zulfikar Hafizd (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2026)
Digital transformation in local government requires legal information services that are transparent, accurate, accessible, and responsive to public needs. This study examines the position and implementation of the Cirebon JEH program within smart governance in Cirebon City and identifies its constraints and optimization strategies. It employs empirical legal research using a socio-legal approach and a qualitative case study design. Data were collected through observation, in-depth interviews with officials from the Legal Division of the Regional Secretariat and the Cirebon City Office of Communication, Informatics, and Statistics, and a review of legislation, policy documents, the Legal Documentation and Information Network, and program publications. The findings indicate that Cirebon JEH functions as a legal service ecosystem comprising JDIH, legal product dissemination, and the development of an Integrated Policy Formulation Coordination System. The program supports information disclosure, service efficiency, bureaucratic coordination, and the dissemination of local legal products. Nevertheless, its implementation remains stronger in one-way transparency than in meaningful public participation. Other constraints include an unclear program identity, limited information technology competence, inconsistent digital document quality, coordination problems, insufficient operational guidelines, and weak user-based evaluation. The study concludes that Cirebon JEH contributes to smart governance but requires institutional integration, information quality control, capacity building, and participatory channels with traceable government responses.